RISE: Potential of fine art logistic industry / Assoc. Prof. Dr Rafeah Legino - Legino, Rafeah (Office of the Deputy Vice-Chancellor (Research & Innovation), 2021)
Fine art logistics are growing gradually in this country as compared to other developed countries.